Passing a budget - Ehman, Ashley M. (How government works (Cavendish Square), 2019)
Examines the steps involved in passing a budget in the U.S. government highlighting how a budget is determined and key budgetary moments in U.S. history. Includes a chronology, a map, a glossary, resources for further information, and color photographs.